Valoración económica del servicio ambiental de secuestro de CO2 en la parcela VII del arboretum "El Huayo" del Centro de Investigación y Enseñanza Forestal de Puerto Almendra, Iquitos. 2021 - Escobedo Vela, Víctor Pablo (2023)
The economic valuation of CO2 sequestration, capture and carbon stored in the study area will help us to reduce emissions and conserve forest resources to balance the environment. The present study aims to economically value the environmental service of CO2 sequestration in plot VII of the Arboretum "El Huayo" of the Forestry Research and Teaching Center of Puerto Almendra, and this study has a descriptive non-experimental quantitative approach. The floristic composition of plot VII has 647 trees in total, being the main species Eschweilera coriacea (8,35%), Iryanthera laevis (7,57%), Protium paniculatum Engl (5,72%), Tapirira guianensis (4,64%) and Iryanthera tessmanii (4.48%). The quantified biomass present in the study plot is 401 549,83 kg, carbon stored 200,77 tC, there is a sequestration of 735,68 tCO2 and an economic value of CO2 sequestration amounting to a total of US$ 63 356,71 and if there is a significant difference in the economic value of the environmental service of CO2 sequestration among the forest species in plot VII.